Accounting, accountants and accountability regimes in pluralistic societies: Taking multiple perspectives seriously. Issue 5 (15th June 2015) - Brown, Judy; Dillard, Jesse; Hopper, Trevor
Abstract : Purpose: – The purpose of this paper is to synthesize work in the emerging field of how accounting and accountability can be reoriented to better promote pluralistic democracy which recognizes and addresses differentials in power, beliefs and desires of constituencies. An agenda for future research and engagement is outlined, drawing on this and insights from other papers in this special issue of the Accounting, Auditing and Accountability Journal ( AAAJ ) aimed at taking multiple perspectives seriously. Design/methodology/approach: – The paper reviews and synthesizes the central themes associated with accounting, accountants and accountability regimes in pluralistic societies, especially with respect to the research studies in this AAAJ special issue, and it identifies possibilities for future research and engagement. Findings: – Three central themes are identified: the challenges of achieving critical, pluralistic engagement in and through mainstream institutions; the possibilities of taking multiple perspectives seriously through decentred understandings of governance and democracy; and the value of an agonistic ethos of engagement in accounting. The articles in this issue contribute to these themes, albeit differently, and in combination with the extant social science literature reviewed here, open up pathways for future research and engagement. Practical implications: – This work seeks to encourage the development of pluralistic accounting and accountability systems drawing on conceptual and practice-based resources across disciplines and by considering the standpoints of diverse interested constituencies, including academics, policymakers, business leaders and social movements. Originality/value: – How accounting can reflect and enact pluralistic democracy, not least to involve civil society, and how problems related to power differentials and seemingly incompatible aims can be addressed has been largely neglected. This issue provides empirical, practical and theoretical material to advance further work in the area.